Analisis Potensi Ekowisata di Hutan Desa Damaran Baru Kabupaten Bener Meriah dengan Menggunakan Metode Analisis ADO-ODTWA: Analysis of Ecoturism Potential of Damaran Baru Village Forest, Bener Meriah Regency Using ADO-ODTWA Analysis Method - Safitri, Oriza; Abbas, Rahmat; Satriawan, Halus (Jurnal Ilmu Ilmu Kehutanan, 2025)
Ecotourism is one of the activities that can be implemented in the Damaran Baru Village Forest. Ecotourism is believed to enhance community well-being and the sustainability of natural resources. The development of ecotourism in Damaran Baru Village Forest must align with the area's functions; therefore, it is essential to understand the characteristics and potential of Natural Tourist Attractions (Obyek dan Daya Tarik Wisata Alam) within it. This research aims to Identify and analyze the potential ODTWA in Damaran Baru Village Forest. The potential natural tourist attractions were analyzed using the Guidelines for the Analysis of Operational Areas - Natural Tourist Attractions (ADO-ODTWA) by the Directorate General of Natural Resources and Ecosystem Conservation (Dirjen PHKA) in 2003. HDDB has the potential for natural tourist attractions worthy of development, but it faces several obstacles and challenges in becoming an ecotourism destination. The results show that HDDB is feasibility to be developed as ecotourism destination based on the recapitulation of potential value of objects and natural attraction with a potential value index of 80,93%. Some criteria that require attention and improvement, so it can be a priority if this Village forest area developed into ecotourism destination. KEYWORD : Forest, Potential, Ecotourism, attractions, natural